Estudo e contole de um robô hexápode utilizando o ROS (Robot Operating System) - Nunes, Victor (2020)
The technological advancements and the search for more productivity and efficiency has been changing the industrial environment, including the adoption of solutions in robotic field. In this scenario the goal of this document is develop a model and control of an hexapod robot, inside ROS (Robot Operating System) environment. The robot is a working project developed for the aircraft industry, inside the concept of 4.0 Industry. The proposal is developing a forward and an inverse kinematic model of the robot and apply them inside the visualization software of ROS, Rviz, to simulate a gait cycle. The kinematic model will be evaluated with the expected trajectory and if is possible for control the robot inside the environment for development of upcoming projects.